2020
DOI: 10.1021/acsaelm.0c00292
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Carbon-Based Flexible Strain Sensors in Physiological Signal Monitoring

Abstract: Flexible strain sensors have attracted much attention due to their good flexibility, high sensitivity, superior repeatability, and great potentials for application in physiological signal detection. Carbon materials, including carbon nanotubes, graphene, carbon black, graphite, and natural-bioderived carbon materials are often used as active materials for the fabrication of flexible strain sensors because of their superior electrical conductivity and flexibility. Among them, carbon nanotubes and graphene can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 118 publications
0
43
0
Order By: Relevance
“…Carbon-based materials are ideal components to build flexible sensors for instance to monitor physiological parameters [ 136 ]. The amino acid cysteine was employed to yield a graphene-hydrogel electrode that was envisaged to monitor pathological states such as diabetes and obesity [ 97 ].…”
Section: Recent Advancements On Hydrogels With Carbon Nanomaterials For Medicinementioning
confidence: 99%
“…Carbon-based materials are ideal components to build flexible sensors for instance to monitor physiological parameters [ 136 ]. The amino acid cysteine was employed to yield a graphene-hydrogel electrode that was envisaged to monitor pathological states such as diabetes and obesity [ 97 ].…”
Section: Recent Advancements On Hydrogels With Carbon Nanomaterials For Medicinementioning
confidence: 99%
“…The historical review by Hughes‐Riley et al [ 8 ] maps the evolution of smart textiles over the past century in terms of first‐, second‐, and third‐generation e‐textiles and presents the broad categories of their application including wearable computing, sensing, energy harvesting, and power transmission. The 2019 and 2020 reviews on flexible activity and electrophysiological sensors by Khair et al, [ 17 ] Heo et al, [ 18 ] and Li et al [ 19 ] provide detailed commentary on the challenges associated with various fabrication technologies and material selection for mainly carbon‐based textile sensors. The current review comes in a timely fashion to build upon the previous work with a bifocal agenda.…”
Section: Introductionmentioning
confidence: 99%
“…However, they cannot be reused and tend to cause skin allergies and other problems [5]. Studies have shown that metallic silver [6], stainless steel wire [7], conductive polymer [8], carbon-based nanomaterial [9], or other composite materials can be used as alternative materials for dry electrodes [10,11]. These materials can be used in place of wet Ag/AgCl electrodes for the detection of ECG physiological signals.…”
Section: Introductionmentioning
confidence: 99%